Membangun Literasi Digital dalam Komunikasi Pembelajaran bagi para Guru SMP Negeri 54 Bandung - Santi Susanti; Wahyu Gunawan (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
The rapid development of digital technology and information has brought significant changes in the way humans communicate and share information, particularly in the educational sector. The ability of educators to adapt to technology in the learning process is absolutely necessary to face the challenges of the 21st century. Digital literacy has become an essential competency for educators in navigating both online and hybrid learning environments. The Community Service (PPM) team from Fikom Unpad implemented a digital communication training program based on social media for instructional learning. The method utilized in this program involved direct face-to-face workshops and the provision of comprehensive materials regarding the utilization of social media and digital platforms in learning. The results of the activity indicate a significant increase in teachers’ understanding of digital literacy concepts, alongside their enhanced ability to integrate digital media into classroom communication effectively and ethically. This program is expected to serve as a sustainable capacity-building model for teachers, ultimately supporting and elevating the quality of education at the junior high school level.